Time-lapse seismic imaging of the Reykjanes geothermal reservoir - Weemstra, C. (author); Obermann, Anne (author); Verdel, Arie (author); Paap, B (author); Blanck, Hanna (author); Guðnason, Egill Árni (author); Hersir, Gylfi Páll (author); Jousset, Philippe (author); Sigurðsson, Ömar (author) (2016)
We report on the results obtained from a dense seismic deployment over a geothermal reservoir located on the tip of the Reykjanes peninsula, SW Iceland. The available seismic stations have continuously recorded the ambient-seismic wave field between April 2014 and August 2015. Using seismic interferometry (SI), seismic responses were generated between these receivers. SI allows one to turn one receiver of a receiver pair into a so-called ‘virtual source’, whose response is then retrieved by the other receiver. The retrieved virtual-source response approximates the medium’s Green’s function between the two receiver locations. For the ambientseismic recordings used in this study, virtual-source retrieval involves simple time-averaging of the crosscorrelations between these recordings. The virtual-source responses were retrieved in a time-lapse manner. The temporal variation of the ‘coda’ of these virtual-source responses has been evaluated, where the term coda refers to the later arriving, multiply scattered waves. The multiple scattering implies that these waves have sampled the subsurface very densely and hence have become highly sensitive to tiny mechanical and structural changes in that subsurface. We did not find a clear relation between the temporal variation of the coda waves and the injection/ extraction rates of the geothermal reservoir. Applied Geophysics and Petrophysics